2005
DOI: 10.1111/j.1547-5069.2005.00027.x
|View full text |Cite
|
Sign up to set email alerts
|

Hopelessness as a Response to Physical Illness

Abstract: Continued study of hopelessness as a psychological response to physical illness is needed, including the continued differentiation of hopelessness from depression, further analysis of the continuum of hopelessness and depression, and the differentiation of state from trait hopelessness. Research to validate this conceptualization will enhance accuracy of the diagnosis of hopelessness and testing of nursing inteventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 27 publications
(60 reference statements)
2
27
0
1
Order By: Relevance
“…Cross-sectional studies have found an association between depression and hopelessness symptoms (Bagge, Lamis, Nadorff, & Osman, 2014). However, hopelessness may also occur independent of depression or as a precursor to depression (Dunn, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Cross-sectional studies have found an association between depression and hopelessness symptoms (Bagge, Lamis, Nadorff, & Osman, 2014). However, hopelessness may also occur independent of depression or as a precursor to depression (Dunn, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the coping response (i.e., hopelessness) may be one of the most important targets for alleviating patients' psychological distress (Akechi, Okuyama, Imoto, Yamawaki, & Uchitomi, 2001). Other than psychiatric studies, the identification of hopelessness attributes in medical research has been more limited than that in psychology or nursing (Dunn, 2005).…”
mentioning
confidence: 99%
“…6 Hopelessness is also one of the most frequent and important conditions described in medically ill patients. 7 The feeling that hopes have been destroyed or that a dilemma cannot be resolved makes hopelessness common in cancer patients. Hopelessness can threaten a patient's physical and psychological well-being and can affect the process of recovery and rehabilitation.…”
mentioning
confidence: 99%